The Utilization Of Artificial Intelligence In Arabic Language Instruction At Islamic Higher Education Institutions - M. Rasyid; Muhammad Yunus Gultom; Andika Novriadi Cibro (International journal of technology and education research, 2026)
Learning Arabic language in Islamic Religious Colleges (PTKI) is facing multidimensional problems rooted in duality its function as Language modern communication at the same time key access to treasury classical Islamic intellectuals, which is exacerbated by heterogeneity ability beginning students, limitations time lectures, as well as Still dominant method pedagogy less conventional​ responsive to personal needs of students. Research This use method studies library or library research with analyze in a way systematic sources Appropriate literature includes:​ book scientific, articles journal reputable, and reports results research, with technique analysis content reinforced qualitative​ triangulation source For ensure data validity. Research results reveal four findings main. First, typology the use of AI has spectrum wide, starting from NLP based grammar checker, speech recognition for pronunciation, conversational chatbots, to adaptive Intelligent Language Tutoring Systems, including application specific For analysis text Islam. Second, AI is proven effective increase skills receptive and aspects mechanistic productive, but its effectiveness moderated by level skills students and not yet capable replace role lecturer on skills level high. Third, AI integration is faced with a dialectic between opportunity personalization mass with challenge gap infrastructure, low AI literacy of lecturers, as well as problem AI accuracy against complexity Arabic and its suitability with manners Islamic science. Fourth, the use of AI gives rise to implications fundamental ethical, pedagogical, and theological principles, including shift role lecturer, crisis integrity academic, as well as urgency framework Islamic ethics for ensure harmony content with faith. The implication is that PTKI needs to formulate human-AI partnership policy through development equitable digital infrastructure, an integrative AI literacy program for lecturers, and the formation of a curatorial body AI- based content Islam.